Development, chemical composition, textural characterization and sensory acceptability of oyster or big cup mushroom incorporated chicken meatloaves - Olabinke, C.K.; Adegoke, A.F.; Sobukola, O.P.; Fafiolu, A.O.; Adebowale, A.R. (2025)
This study examined chemical and textural attributes as well as sensory acceptability of chicken and mushroom (oyster and big cup) meatloaves. Simplex lattice design was used to create eight formulations of chicken-oyster mushroom (COM) and chicken-big cup mushroom (CBM), respectively. The samples were analyzed for proximate and mineral composition, crust and crumb color, pH, and texture. The optimized meatloaf samples were subjected to sensory evaluation. The optimized chicken-mushroom ratios were determined to be 83.82% chicken meat and 16.18% oyster mushroom, and 84.78% chicken meat and 15.22% big cup mushroom. Chicken-oyster meatloaf was rated as more acceptable than chicken-big cup meatloaf and control samples in all aspects by sensory panelists. There was no significant difference (p > 0.05) between the sensory attributes, except for aroma (p < 0.05). The study concluded that inclusion of oyster or big cup mushroom in chicken meatloaf had significant influence (p < 0.05) on nutritional, color, pH, and texture characteristics of chicken meatloaf.